Predictive value of ibutilide response for postoperative recurrence following catheter ablation in persistent atrial fibrillation: a retrospective study - Ma, Liuling; Lai, Renkui; Guo, Zhehan; Cai, Tianjin; Huang, Jingyi; Li, Jinxin (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis study investigated efficacy of intraoperative ibutilide administration for cardioversion of persistent atrial fibrillation (AF) during catheter ablation and evaluated predictive factors for postoperative AF recurrence.MethodsA retrospective analysis was conducted involving 111 patients with persistent AF who underwent radiofrequency catheter ablation. Patients who failed to restore sinus rhythm after ablation received intravenous ibutilide (1–2 mg). Patients achieving sinus rhythm post-ibutilide administration were categorized as responders, while non-responders underwent electrical cardioversion. Clinical data were collected, and logistic regression was utilized to identify factors associated with ibutilide response and postoperative AF recurrence.ResultsSinus rhythm was restored by ibutilide in 73 patients (65.7%). Non-response to ibutilide was independently associated with longer AF duration (OR = 1.82), diabetes ellitus (OR = 2.27), coronary artery disease (OR = 2.56), increased ST2 (OR = 1.08), larger left atrial diameter (LAD) (OR = 1.25), elevated NT-proBNP (OR = 1.01), and higher CHA2DS2-VASc scores (OR = 1.96; all P < 0.05). AF recurrence within 3 months post-ablation was independently predicted by intraoperative ibutilide non-response (OR = 5.317), older age (OR = 1.213), diabetes mellitus (OR = 0.14), increased LAD (OR = 1.211), elevated ST2 (OR = 1.139), elevated hs-CRP (OR = 1.276), and higher CHA2DS2-VASc scores (OR = 2.736; all P < 0.05).ConclusionIntraoperative ibutilide responsiveness significantly predicts postoperative AF recurrence in patients undergoing catheter ablation for persistent AF. Assessing ibutilide response may enhance risk stratification and guide personalized treatment strategies.